2019
DOI: 10.1038/s41594-019-0270-6
|View full text |Cite
|
Sign up to set email alerts
|

The nascent RNA binding complex SFiNX licenses piRNA-guided heterochromatin formation

Abstract: The PIWI-interacting RNA (piRNA) pathway protects genome integrity in part through establishing repressive heterochromatin at transposon loci. Silencing requires piRNA-guided targeting of nuclear PIWI proteins to nascent transposon transcripts, yet the subsequent molecular events are not understood. Here, we identify SFiNX (Silencing Factor interacting Nuclear eXport variant), an interdependent protein complex required for Piwi-mediated co-transcriptional silencing in Drosophila. SFiNX consists of Nxf2-Nxt1, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
149
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(170 citation statements)
references
References 80 publications
(122 reference statements)
17
149
0
Order By: Relevance
“…This is because we performed our analysis using cultured cell line OSCs, and took different timepoints after expression of Nxf2 (Fig ). The present study is the only one to consider time points as early as 48 h. The regulation observed at 96 h after transfection, representing later stages of TE silencing, was consistent with the observation by Batki et al (preprint: Batki et al , ). An important issue to be clarified is the mechanism by which the PPNP complex initiates the silencing of TEs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is because we performed our analysis using cultured cell line OSCs, and took different timepoints after expression of Nxf2 (Fig ). The present study is the only one to consider time points as early as 48 h. The regulation observed at 96 h after transfection, representing later stages of TE silencing, was consistent with the observation by Batki et al (preprint: Batki et al , ). An important issue to be clarified is the mechanism by which the PPNP complex initiates the silencing of TEs.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we all have shown that the UBA domain of Nxf2 associates with Panx, and the NTF2 domain associates with p15. Our group and Batki et al have shown that the first LRR domain with RNA binding activity is needed for the regulation of TEs (preprint: Batki et al , ), and we have further shown direct association of TE transcripts with Nxf2 (Fig ). Among these four groups, we were the only one which was able to observe the initial steps of the silencing.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Aub and Ago3 are cytoplasmic and repress transposons post-transcriptionally [12,13]. Piwi is localized in the nucleus and represses transposons transcriptionally with co-factors, including Panoramix (Panx), Gtsf1, Nxf2, Nxt1/p15, Maelstrom (Mael), Eggless (Egg), histone linker H1, and HP1 [2,7,12,14,15,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: The Pirna Pathway In Drosophila Ovaries: the Outlinementioning
confidence: 99%